The Authority Of The Indonesia Constitutional Court In Revi Ew Of Law Against Basic Law - Yulianto, Winasis (International Journal of Educational Research & Social Sciences, 2023)
The Constitutional Court of the Republic of Indonesia is a State Institution as a product of the Third Amendment to the 1945 Constitution of the Republic of Indonesia. The Third Amendment stipulates that the Constitutional Court of the Republic of Indonesia must have been established on August 17, 2003.Article 24C paragraph (1) Constitution of the Republic of Indonesia year 1945 stipulates that The Constitutional Court has four powers and one obligation. First review: a .to review the law against the constitution, b. resolve disputes between state institutions whose authority is granted by the Constitution, c. dissolve a political party d. resolve disputes over election results. Meanwhile, one obligation of the Constitutional Court is to decide on the opinion of the DPR that the President is based on the opinion of the DPR regarding alleged violations of the law by the president and vice president according to the Constitution. But this research just discussed the first authority, namely to review the law to Basic Law. This research is a normative legal research using various legal norms as an analysis material. Conclusions are drawn using legal interpretation.